Women’s Empowerment and DBM-Relevant Nutrition Outcomes in South Asia: A Systematic Review - Nure Jannat Arpa; Tanvir Ahmed; Sanzana Islam; Aditya Shafy Chandra (Journal of Emerging Global Health, 2026)
Background: The double burden of malnutrition (DBM) is an increasing public health concern in South Asia, where undernutrition persists alongside rising overweight and obesity. Women’s empowerment may influence nutrition through education, decision-making autonomy, mobility, resource control, and economic participation. However, direct evidence linking empowerment to DBM remains limited, and much of the available evidence concerns DBM-relevant nutrition outcomes. Methods: This systematic review followed PRISMA 2020 guidelines. Peer-reviewed empirical studies published between January 2010 and December 2025 were searched in Scopus, Web of Science, and PubMed. Studies conducted in South Asian countries were included if they examined at least one dimension of women’s empowerment in relation to undernutrition, overnutrition, or other DBM-relevant nutrition outcomes. Due to variation in study designs, empowerment measures, and nutrition indicators, findings were synthesized narratively. Results: Fifteen studies met the inclusion criteria. Women’s education, economic empowerment, decision-making autonomy, and access to resources were generally associated with improved undernutrition-related outcomes, including lower stunting, wasting, underweight, anemia, and poor dietary diversity among women and children. Evidence on overweight and obesity was mixed. Some studies suggested that higher education, autonomy, wealth, or improved socioeconomic position were associated with higher BMI or overweight among women, particularly in urban and socioeconomically advantaged settings. Conclusions: Women’s empowerment appears to support improvements in several undernutrition-related outcomes in South Asia. Its relationship with overnutrition is more context-specific. Future research should directly examine DBM within individuals and households using clearer empowerment measures and stronger longitudinal designs.